Extending the generality of leaf economic design principles in the cycads, an ancient lineage - Zhang, Yong Jiang (2015)
Summary: Cycads are the most ancient lineage of living seed plants, but the design of their leaves has received little study. We tested whether cycad leaves are governed by the same fundamental design principles previously established for ferns, conifers and angiosperms, and characterized the uniqueness of this relict lineage in foliar trait relationships. Leaf structure, photosynthesis, hydraulics and nutrient composition were studied in 33 cycad species from nine genera and three families growing in two botanical gardens. Cycads varied greatly in leaf structure and physiology. Similarly to other lineages, light-saturated photosynthetic rate per mass (Am) was related negatively to leaf mass per area and positively to foliar concentrations of chlorophyll, nitrogen (N), phosphorus and iron, but unlike angiosperms, leaf photosynthetic rate was not associated with leaf hydraulic conductance. Cycads had lower photosynthetic N use efficiency and higher photosynthetic performance relative to hydraulic capacity compared with other lineages. These findings extend the relationships shown for foliar traits in angiosperms to the cycads. This functional convergence supports the modern synthetic understanding of leaf design, with common constraints operating across lineages, even as they highlight exceptional aspects of the biology of this key relict lineage.